Improving the Role of Students in Teaching Campus Leraning 4 Introduction of Numbers in Mandarin Language in Students of SMP Gadjah Madan Medan - Elly Romy; Kiki Goslim; Wenny; Ivana; Cynthia Hualangi (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2023)
Language is a distinctive sign that distinguishes humans from other creatures and is used as a communication interaction. Language can differ from one country to another and from one tribe to another. Language shows the nation and the people who live in it, language can show how strong and how independent a nation is and how classy a nation is in its time. The objectives of implementing this Community Service activity are 1. To increase awareness of students at Gadjah Mada Middle School in Medan, 2. To provide students with an understanding of basic learning of numbers in Mandarin, 3. To provide moral and material support for students in blending in with the community various tribes and ethnicities., 4. Instill One Family World Values ​​through Information and Communication Technology. The target of this community service is Gadjah Mada Middle School students consisting of class VII, VIII and class IX. This Community Service activity is a visit and socialization with the theme Increasing the Role of Students in the Teaching Campus 4 Introduction to Numbers in Mandarin for Students of SMP Gadjah Madan Medan. The outputs generated from this Community Service are documentation about socialization and learning for students and reports as proof of community service that are published in the Community Service Journal institution.